2018
DOI: 10.1007/s12144-018-9948-x
|View full text |Cite
|
Sign up to set email alerts
|

Dark malevolent traits and everyday perceived stress

Abstract: Stress is a factor that greatly impacts our lives. Previous research has examined individual differences in relation to stress. However, research regarding malevolent personality traits in relation to how stress is perceived is limited. The purpose of the present study was to investigate relationships between dark malevolent personality traits; psychopathy (EPA), Machiavellianism (MACH-IV), vulnerable narcissism (HSNS), grandiose narcissism (NPI-13), and perceived stress (PSS-10) in a community sample (N = 346… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 43 publications
1
17
1
Order By: Relevance
“…Regarding psychopathy, specifically, the unanticipated findings may be due to trait scores being asymmetrically distributed and below the population mean (Jones & Paulhus, 2014). Consistent with previous research, no associations were found between Machiavellianism and stress (Kajonius & Björkman, 2018;Noser et al, 2014) nor cognitive performance (McInerney, 2018).…”
Section: Personality Stress and Performancesupporting
confidence: 72%
See 3 more Smart Citations
“…Regarding psychopathy, specifically, the unanticipated findings may be due to trait scores being asymmetrically distributed and below the population mean (Jones & Paulhus, 2014). Consistent with previous research, no associations were found between Machiavellianism and stress (Kajonius & Björkman, 2018;Noser et al, 2014) nor cognitive performance (McInerney, 2018).…”
Section: Personality Stress and Performancesupporting
confidence: 72%
“…Psychopathy has been found to predict self-reported stress both favorably (Kajonius & Björkman, 2018;McInerney, 2018) and adversely (Noser et al, 2014;Wendt & Bartoli, 2019), with different psychopathy dimensions being potentially more advantageous than others (Wendt & Bartoli, 2019). Narcissism has been linked to stress-reactivity, though the direction of this link may also depend on the dimension of narcissism explored (Coleman et al, 2019).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Each of these are quite different and can alter behaviour in different ways (e.g. Kajonius & Björkman, 2018). Psychopathy too can be separated into several sub-scales depending on the measure used.…”
Section: Methodological Issues and Considerations For Subsequent Studiesmentioning
confidence: 99%